Children With Autism Spectrum Disorder and Neurodevelopmental Regression Present a Severe Pattern After a Follow-Up at 24 Months - Martin-Borreguero, Pilar; Gómez-Fernández, Antonio Rafael; De La Torre-Aguilar, Maria Jose; Gil-Campos, Mercedes; Flores-Rojas, Katherine; Perez-Navero, Juan Luis (Frontiers in Psychiatry, 2021)
This study examined the presence of neurodevelopmental regression and its effects on the clinical manifestations and the severity of autism spectrum disorder (ASD) in a group of children with autism compared to those without neurodevelopmental regression, at the time of initial classification and subsequently. Methods and Subjects ASD patients were classified into two subgroups: neurodevelopmental regressive (AMR) and non-regressive (ANMR), using a questionnaire based on the Autism Diagnostic Interview-Revised test. The severity of ASD and neurodevelopment was assessed with the Childhood Autism Rating Scale Test-2, Strengths and Difficulties Questionnaire, Pervasive Developmental Disorders Behaviour Inventory Parent Ratings (PDDBI) and with the Battelle Inventory tests at the beginning of the study and after 24 months of follow-up. Fifty-two patients aged 2 to 6 years with ASD were included. Nineteen were classified with AMR, and 33 were classified with ANMR. Results The AMR subgroup presented greater severity of autistic symptoms and higher autism scores. Additionally, they showed lower overall neurodevelopment. The AMR subgroup at 24 months had poorer scores on the Battelle Inventory Test in the following areas: Total personal/social (p<0.03), Total Motor (p<0.04), Expressive (p<0.01) and Battelle Total (p<0.04). On the PDDBI test, the AMR subgroup had scores indicating significantly more severe ASD symptoms in the variables: ritual score (p<0.038), social approach behaviours (p<0.048), expressive language (p<0.002) and autism score (p<0.003). Conclusions ASD patients exhibited a set of different neurological phenotypes. The AMR and ANMR subgroups presented different clinical manifestations and prognoses in terms of the severity of autistic symptoms and neurodevelopment.